Clostridium difficile-associated disease - V. T. Ivashkin; O. S. Shifrin; A. S. Tertycnhy; Ye. A. Poluektova; T. L. Lapina; O. S. Lyashenko; K. V. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To generalize accumulated data on C. difficile infection, diagnostics, treatment and prevention of C.difficile-associated disease.Summary. C.difficile is unthrifty on breeding grounds, obligate anaerobic, gram-positive, sporeforming, cytotoxin-producing bacterium. C. difficile toxins A and B are protein molecules, classified as glycosyltransferases. Influence of toxins induces damage and inflammation of intestinal wall due to impairment of intestinal epithelial barrier, stimulation of proinflammatory cytokine production, apoptosis and necrosis of epithelial cells. Basic clinical symptom of C. difficileassociated disease is diarrhea or diarrhea with hematochezia (according to severity of the case). Feces of patients with diarrhea are sampled for C. difficile toxin detection. Nowadays there are several laboratory diagnostic tests for Clostridial infection: testing for C. difficile glutamate dehydrogenase, enzyme-linked immunoassay, polymerase chain reaction for toxigenic strain of C. difficile. However, which of these methods may be considered to be «the gold standard» is unclear yet. Metronidazole, vancomycin, dioctaedric smectite and probiotics are used for treatment of C. difficile infection. Rational use of antibiotics, shortening of hospital stay terms whenever possible, especially for patients of 65 years of age and older is recommended to reduce the risk of clostridial infection development. Preliminary, routine and general cleaning should be carried out in medical institutions as well as the cleaning of hands of medical personnel and medical stock according to sanitary-and-epidemiologic rules and specifications.Conclusion. From the beginning of XXI century in many countries of the world prompt increase of C. difficile-associated disease cases is marked. This disease is the most frequent cause of intrahospital diarrhea resulting in significant mortality. This is why it is extremely important to be able to diagnose, treat in due terms this disease and to carry out prophylactic procedures.